HUBUNGAN ANTARA KECERDASAN VERBAL LINGUISTIK DAN MOTIVASI MEMBACA DENGAN KETERAMPILAN MEMBACA PEMAHAMAN - Fitria Almaratush Sholihah; Budhi Setiawan (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to determine the contribution of the two independent variables to students’ reading comprehension skills. The research method used was quantitative correlational research. The population in this study consisted of all eleventh-grade students of SMK Negeri 2 Surakarta, with a sample of 79 students selected using a simple random sampling technique. Data were collected through tests and non-test instruments. The data analysis techniques included prerequisite tests of analysis and multiple linear regression statistical tests to examine both partial and simultaneous contributions.The results of the study showed that there was a positive and significant simultaneous relationship between verbal linguistic intelligence and reading motivation with news text reading comprehension skills. The higher the students’ level of verbal linguistic intelligence and reading motivation, the better their ability to deeply understand the content of news texts. The conclusion of this study confirms that cognitive and affective factors play an important role in improving reading competence at the vocational high school level.